Understanding lymphocyte metabolism for use in cancer immunotherapy. (17th April 2018) - MacPherson, Sarah; Kilgour, Marisa; Lum, Julian J.
Abstract : Like all dividing cells, naïve T cells undergo a predictable sequence of events to enter the cell cycle starting from G0 and progressing to G1, S and finally G2 /M. This methodical series of steps ensures fidelity in the generation of two identical T cells during a single round of division. To achieve this, T cells must activate or inactivate metabolic pathways at discrete times during each phase of the cell cycle. This permits the generation of substrates to support biosynthesis, bioenergetics and the epigenetic changes required for proper differentiation and function. The precursors that feed into these pathways are often shared, highlighting the complex relationship between metabolism and cellular processes that are essential to lymphocytes. It is therefore not surprising that different T cell subtypes exhibit unique metabolic dependencies that change as they mature and go through specialized differentiation programmes. The importance of the influence of metabolism on T cells is underscored by the emerging field of cancer immunotherapy, where autologous T cells can be manufactured ex vivo then infused as a form of curative treatment for human cancers. This review will highlight some of the recent knowledge on T lymphocyte metabolism and give a perspective on the practical implications for cellular‐based immunotherapy. Abstract : T cells must activate or inactivate metabolic pathways at discrete times during each phase of the cell cycle and exhibit unique metabolic dependencies as they mature. This review highlights some of the recent knowledge on T lymphocyte metabolism and gives a perspective on the practical implications for cellular‐based immunotherapy.